Kostadin Kisyov, Thrace and Greece in ancient times, Part 1, Classcal age tumuli in the municipality of Kaloyanovo, Plovdiv 2005, σελ. 1-119, πίν. Ι – ΧΧΙΧ - Τιβέριος Μιχάλης Α. (Μακεδονικά, 2011)
no abstract